2006
DOI: 10.1007/s10826-006-9020-6
|View full text |Cite
|
Sign up to set email alerts
|

Family Factors Predicting Categories of Suicide Risk

Abstract: We compared family risk and protective factors among potential high school dropouts with and without suicide-risk behaviors (SRB) and examined the extent to which these factors predict categories of SRB. Subjects were randomly selected from among potential dropouts in 14 high schools. Based upon suicide-risk status, 1,083 potential high school dropouts were defined as belonging to one of four groups; 573 non-suicide risk, 242 low suicide risk, 137 moderate suicide risk and 131 high suicide risk. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 33 publications
1
35
0
12
Order By: Relevance
“…Similarly, using a sample of Hispanic adolescents who were either immigrants themselves, or who had at least one immigrant parent, Portes and Zady [36] also found a direct relationship between parent and child conflict and both lower selfesteem levels, and higher depression levels. Some research has also shown a direct relationship between parent-adolescent conflict and suicide attempts [37,38]. Conflict in the dyad as expressed through serious fights [39], parental criticism [40], and unresolved conflicts between the adolescents and their parents [41] have all been found to distinguish suicidal adolescents from their non-suicidal peers.…”
Section: Development Conflict and Culturementioning
confidence: 99%
“…Similarly, using a sample of Hispanic adolescents who were either immigrants themselves, or who had at least one immigrant parent, Portes and Zady [36] also found a direct relationship between parent and child conflict and both lower selfesteem levels, and higher depression levels. Some research has also shown a direct relationship between parent-adolescent conflict and suicide attempts [37,38]. Conflict in the dyad as expressed through serious fights [39], parental criticism [40], and unresolved conflicts between the adolescents and their parents [41] have all been found to distinguish suicidal adolescents from their non-suicidal peers.…”
Section: Development Conflict and Culturementioning
confidence: 99%
“…Serious fights with family mem� bers were significantly associated with increased risk of suicide attempts in late adolescence or early adulthood [43]. Yet it remains difficult to determine the contribu� tion of parent�adolescent conflict to adolescent suicide� risk behavior, given the association of these conflicts with adolescent psychological problems [44,45]. The prevalence of exposure to violence is relatively unex� plored in adolescents in European communities and re� ports on the association between exposure to commu� nity violence and suicidal behavior are rare [46].…”
Section: Discussionmentioning
confidence: 99%
“…Common precursors to suicide-related behavior include rejection by a boyfriend or girlfriend or disruption in the romantic relationship (Hjelmeland & Groholt, 2005), conflict with parents (Randell, Wang, Herting, & Eggert, 2006), trouble with school or work (Hawton, O'Grady, Osborn, & Cole, 1982), increased arguments with friends or fighting with siblings (Eyeman, 1987), and loss of a family member (Freuchen, Kjelsberg, & Groholt, 2012). Precipitating conditions also consist of moving (Qin, Mortensen, & Pedersen, 2009), homelessness (Ganz & Sher, 2012), problems with the police and legal difficulties (Hoberman & Garfinkel, 1988), and bullying (Luukkonen, Rasanen, Hakko, & Riala, 2009).…”
Section: E Bocciomentioning
confidence: 99%